Differential root and shoot magnetoresponses in Arabidopsis thaliana - Ivan A. Paponov (Nature Portfolio, 2021)
Abstract The geomagnetic field (GMF) is one of the environmental stimuli that plants experience continuously on Earth; however, the actions of the GMF on plants are poorly understood. Here, we carried out a time-course microarray experiment to identify genes that are differentially regulated by the GMF in shoot and roots. We also used qPCR to validate the activity of some genes selected from the microarray analysis in a dose-dependent magnetic field experiment. We found that the GMF regulated genes in both shoot and roots, suggesting that both organs can sense the GMF. However, 49% of the genes were regulated in a reverse direction in these organs, meaning that the resident signaling networks define the up- or downregulation of specific genes. The set of GMF-regulated genes strongly overlapped with various stress-responsive genes, implicating the involvement of one or more common signals, such as reactive oxygen species, in these responses. The biphasic dose response of GMF-responsive genes indicates a hormetic response of plants to the GMF. At present, no evidence exists to indicate any evolutionary advantage of plant adaptation to the GMF; however, plants can sense and respond to the GMF using the signaling networks involved in stress responses.